2012
DOI: 10.36076/ppj.2012/15/415
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Transforaminal Epidural Steroid Injection by the Conventional Technique in FarLateral Herniation of Lumbar Disc

Abstract: Background: Owing to the anatomical difference between the far lateral herniation of the lumbar disc (FHLD) and the intraspinal herniation of lumbar disc (iHLD), the outcome of transforaminal epidural steroid injections (TFESI) in patients with FHLD seems to be different from that in patients with iHLD. However, few studies have evaluated the efficacy of TFESI in FHLD. Objective: To evaluate and compare the efficacy of TFESI in FHLD and iHLD patients. Study Design: A retrospective design. Methods: There were 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The injectate diffuses from the spinal nerve root to the lateral recess, resulting in a slow effect and weak efficacy, which leads to less satisfaction. Moreover, a retrospective study[ 7 ] reported that LRB was considerably safer, with a lower chance of nerve pricks[ 19 ] and intravascular dye spread than CTFESI. This study also revealed that a single LRB was significantly better than a single CTFESI in decreasing unilateral radiculopathy pain because the site of drug deposition was more proximal to the discovery interface.…”
Section: Discussionmentioning
confidence: 99%
“…The injectate diffuses from the spinal nerve root to the lateral recess, resulting in a slow effect and weak efficacy, which leads to less satisfaction. Moreover, a retrospective study[ 7 ] reported that LRB was considerably safer, with a lower chance of nerve pricks[ 19 ] and intravascular dye spread than CTFESI. This study also revealed that a single LRB was significantly better than a single CTFESI in decreasing unilateral radiculopathy pain because the site of drug deposition was more proximal to the discovery interface.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [ 19 ] evaluated 15 and 70 patients in the FLLDH and intraspinal herniation of lumbar disc groups with fluoroscopically guided TFSI. They found significant improvement in the VAS and ODI score demonstrated in the FLLDH group 12 weeks after injection; moreover, they concluded that there was no statistically significant difference in the VAS and ODI between both the FLLDH and intraspinal disc group [ 19 ].…”
Section: Discussionmentioning
confidence: 99%